x=(x)(x-3)(x+12)

Simple and best practice solution for x=(x)(x-3)(x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=(x)(x-3)(x+12) equation:



x=(x)(x-3)(x+12)
We move all terms to the left:
x-((x)(x-3)(x+12))=0
We multiply parentheses ..
-(x(+x^2+12x-3x-36))+x=0
We calculate terms in parentheses: -(x(+x^2+12x-3x-36)), so:
x(+x^2+12x-3x-36)
We multiply parentheses
x^3+12x^2-3x^2-36x
We do not support expression: x^3

See similar equations:

| 4d/9d+1/9=2/3 | | 4x+12-2x=18+2x-3 | | 20x=75000 | | 1570=12×h | | 1=(m-3/4)+(m+3/5) | | 4-5x-39=0 | | 36-5x-x2=36 | | 2n-2+12=4n | | (5x+5)+73+67=180 | | 5x+7x=2x+30 | | 2n-2-12=4n | | 15x=7=12x-5 | | 8k^2-10k-10=0 | | 7.3^2=2x^2 | | Tx1/3=7/10 | | 6y+5y=8y+11 | | 6y+5y=8y×11 | | X+0.17x=1200 | | 4y+2=(y-2)=8 | | 2x+8-5x= | | 6x+(x+20)+8x+10=90 | | 4a+3a+6=20 | | 7+6x=-6x-101 | | 6x-(-15)=3 | | 8-2x=4+x | | 7x-7=9x+5 | | 6x+9=44+x | | 75/y;y=5 | | 12n=13n | | -9=0.76a | | -3/8(16x-8)=4 | | 5y+39=3y+85 |

Equations solver categories